Efektivitas Implementasi Program Gerakan Desa Membangun (GDM) dalam Rangka Pemberdayaan Masyarakat di Kabupaten Bungo, Jambi - Fajar Ifan Dolly (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The GDM program is a concrete step by the Bungo Regency government in order to improve welfare, providing opportunities for village economic development. As well as increasing the capacity of the community through various village-level organizations and providing opportunities to the village government for the potential that exists in the village so that it can further be developed into the village's economic strength. This study discusses how to implement and handle GDM programs in the context of community empowerment in Bungo District. This research uses a qualitative method with descriptive analysis. Data analysis techniques using the model of Miles and Huberman. Furthermore, this study uses a data validity experiment using the Triangulation Method, namely by comparing information or data in different ways to obtain the correctness of information. The results showed how the implementation of community empowerment in Bungo District did not go well so it did not create opportunities for the community to become more empowered and protect the weak groups. The implementation of empowerment was also not carried out It is expected that what is stated in the regent's regulation regarding the GDM program. This is because the village government focuses more on village infrastructure development and does not focus on empowerment activities. The flow of submission and implementation of village community empowerment activities through groups also does not involve and involve the youth organization as a forum for discussion of the various needs of groups in the village community.